SSU+ITS rRNA gene sequences, and associated metadata, of the larger benthic foraminifera Amphistegina lobifera across its invasive range - Raposo, Débora; Zufall, Rebecca A; Caruso, Antonio; Titelboim, Danna; Abramovich, Sigal; Hassenrück, Christiane; Kucera, Michal; Morard, Raphael (PANGAEA, 2022)
The larger benthic foraminifera species Amphistegina lobifera has been successfully invading the Mediterranean Sea, despite different temperature regimes from their original source location in the Red Sea. To investigate possible genetic (pre)adaptations in the invasive populations, we analyzed the population structure of Amphistegina lobifera across the invasive range (source, pioneer invaders, and invasion front). We snorkelled at four sites across the invasive range to collect living foraminifera individuals attached to macroalgae and pebbles. Each individual was isolated and stored at -80°C until DNA extraction. We amplified the SSU and the hypervariable ITS rRNA 18S gene regions and purified the PCR products. The purified PCR products were cloned, a final PCR was performed and the samples were sent for Sanger sequencing. We compared our results to other populations across the globe (for which only the SSU region is available). Our dataset includes the sequences of the SSU+ITS rRNA regions, which are available on NCBI under the accession numbers OP610171-OP610543, and the associated metadata.
Keywords: Benthic foraminifera; invasion; Lessepsian migration; Mediterranean Sea; population structure